Pola Asuh Orang Tua dan Implikasinya Terhadap Pendidikan Akhlaq di Masyarakat Petani - Imam Hasan Masduqi; Istikomah Istikomah (Cendekia, 2023)
This study aims to determine the parenting style of parents and its implications for moral education in a case study farming community in Banjareja Village, Nusawungu sub-district, Cilacap district. This research is a type of qualitative research with a positivist approach. Data collection is done by observation, and interviews. Those interviewed included village heads, parents, Koran teachers, local communities and children who were used as research subjects. After the data is collected, it is then analyzed, the rare steps of which include collecting data, sorting data and drawing conclusions. From the data analysis, a conclusion was drawn which stated that most of the people of Banjareja Village chose democratic parenting for their children's moral education. Because this democratic parenting style has the advantage that children and parents have a forum for opinions so that they find a middle way to be able to decide a problem. This parenting style is also due to the background of parents who are busy so if they choose an authoritarian parenting style, what happens is that the child will rebel or be permissive, it will happen that the child becomes difficult for parents to manage. So that this democratic parenting style is a good choice for educating children in farming communities.